Hubungan Faktor Pekerjaan Dengan Keluhan Gangguan Otot Dan Tulang Rangka Akibat Kerja Pada Pekerja Laundry - Novianus, Cornelis; Salsabila, Ika Fauziah; Inaku, Awaluddin Hidayat Ramli (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Complaints of muscle and skeletal disorders are diseases and injuries that affect the body's movement system collectively, caused by static loads and repetitive work over a long period of time. One job that has the potential to experience complaints of muscle and skeletal disorders is workers in laundry facilities. Laundry work involves a lot of extra energy and a repetitive flow of tasks such as sorting, weighing, washing, drying, finishing and distributing. This is what leads to the development of occupational risk factors, which can result in musculoskeletal disorders. The aim of the research is to see the relationship between work factors and complaints of muscle and skeletal disorders due to work in laundry workers. Methodology: This research is quantitative analytical with a cross sectional design. The population of this study was 60 laundry workers. The sample was determined using saturated sampling or total sampling by filling out questionnaires, interviews and observations in data collection. Data analysis uses frequency distribution. The research results showed that 85% of respondents experienced complaints of muscle and skeletal disorders and there was a significant relationship between workload (pvalue = 0.029) and work attitude (pvalue = 0.025). This research's advice for laundry workers is that it can prevent and minimize complaints of muscle and skeletal disorders, workers should stretch or exercise their muscles before work, get enough rest after work and take vitamins.